2007
DOI: 10.1016/j.brainres.2007.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of paraquat in microglial cells: Involvement of PKCδ- and ERK1/2-dependent NADPH oxidase

Abstract: Excess production of reactive oxygen species (ROS) is an important mechanism underlying the pathogenesis of a number of neurodegenerative diseases including Parkinson's disease (PD) which is characterized by a progressive loss of dopaminergic neurons in the substantia nigra. Exposure to paraquat, an herbicide with structure similar to the dopaminergic neurotoxin, 1-methyl-4-phenylpyridinium (MPP + ), has been shown to produce PD-like symptoms. Despite previous focus on the dopaminergic neurons and signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 73 publications
2
55
0
Order By: Relevance
“…PKC is involved in the ligand-initiated assembly of NADPH oxidase (NOX) for the generation of superoxide anions (Martins et al, 2002). Recently, paraquat has been shown to induce ROS through activation of PKC-delta dependent NOX (Miller et al, 2007). In addition, mitochondria are involved in paraquat-induced oxidative stress and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…PKC is involved in the ligand-initiated assembly of NADPH oxidase (NOX) for the generation of superoxide anions (Martins et al, 2002). Recently, paraquat has been shown to induce ROS through activation of PKC-delta dependent NOX (Miller et al, 2007). In addition, mitochondria are involved in paraquat-induced oxidative stress and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Although environmental and genetic factors contribute to PD development, the exact etiology remains unclear yet (Gasser, 2005; Sun et al., 2010). Recent studies showed that neurotoxic agents are possible inducers of PD such as manganese (Sun, Yang, & Kim, 1993), dimethoxy phenyl‐ethylamine (Koshimura et al., 1997), paraquat (Miller, Sun, & Sun, 2007), and 1‐methyl‐4‐phenyl‐1, 2, 3,6‐tetrahydropyridine (MPTP) causing oxidative stress, and also mitochondrial dysfunction (Alvira et al., 2007) and inflammation are important factors in dopaminergic neurons degeneration in PD (Giasson, Ischiropoulos, Lee, & Trojanowski, 2002; Sun et al., 2010). Mitochondrial dysfunction plays an important role in the pathogenesis of PD.…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%
“…PKC isoforms have been implicated in the generation of superoxide anions via NOX activation (Miller et al, 2007). Western blot analysis with antiphospho-PKC antibodies was carried out to examine the phosphorylation status of specific PKC isoforms in mouse lung after PQ treatment.…”
Section: Dds Inhibits Pq-induced Pkcμ Activation and Superoxide Anionmentioning
confidence: 99%
“…Notably, NADPH oxidases, NOX2 and NOX4, are predominantly expressed in lung tissues (van der Vliet, 2008;Hecker et al, 2009). Moreover, protein kinase C (PKC) participates in the ligand-initiated assembly of NOX, which proceeds the generation of superoxide anions (Miller et al, 2007). Among more than 20 different PKC isoforms present in mammalian cells, several PKC isoforms are already reported to be linked with expression or activation of NOX; such as PKC μ in lung (Rennecke et al, 1996), PKC δ in mouse adipocytes (Talior et al, 2005) and microglial cells (Miller et al, 2007), and PKC α in human endothelial cells (Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation